TRISEР 2024: Trisakti International Student Exchange Program - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
The relationship between UiTM Sarawak Branch and Universitas Trisakti, Indonesia is further enhanced with the Trisakti International Students Exchange Program (TRISEP), a student outbound mobility program hosted by Universitas Trisakti, Indonesia. Two exceptional students from the Faculty of Sports Science and Recreation, Mei Hui Anak PaulSoon and Izzati Najwa Mohd Yusof participated in the exchange program from August 1st to August 6th, 2023. This programme provided a unique opportunity for these talented individuals to explore new cultures, broaden their horizons, and establish meaningful international connections. Mdm Asmalini Haji Che Abu Shafie, the Head of Academic (Sports Science and Recreation), and Ms. Patricia Pawa Pitil, the accompanying lecturer, were among the distinguished faculty members who graced the meeting. Additionally, Dr. Wan Juliana Emeih Wahed, the Coordinator of the Department of International Affairs, attended the event. highlighting the significance of this student exchange initiative.